A Research Study to Increase Usage of PVs in Residential Areas - Kiray, Vedat (Frontiers in Energy Research, 2021)
There are many obstacles for houses in residential areas to generate their own energy. When these barriers are considered in terms of PV Solar energy use, problems related to the location, slope, strength, and shade exposure of house roofs are the most common. Therefore, it is not possible to meet daily energy needs from PV panels placed on the existing roofs of many houses. Solar Tracking systems keep PV panels perpendicular to the Sun throughout the day, providing a significant increase in their efficiency. But the use of these systems on the roofs or gardens of the houses is not suitable for some reasons, especially in terms of aesthetic appearance. In this article, it is aimed to show effectively how the slope and direction inconsistencies in the existing roofs of houses in residential areas cause great losses in terms of the performance of PVs, and also a research and design study is presented to find a solution to use Sun tracking systems in residential areas without creating aesthetic appearance problem. As a solution, combining a dual axis Sun tracking system with an aesthetic looking Gazebo has been considered. A design study was carried out for the targeted system and it was investigated how much of a movable platform / roof such a system should have in order to meet the electricity needs of a house from the sun throughout the year How much energy the PV panels can collect annually is determined by a simulation program called "PV performance tool".